2011
DOI: 10.1111/j.1365-2966.2011.18714.x
|View full text |Cite
|
Sign up to set email alerts
|

Accretion states of the Galactic microquasar GRS 1758−258

Abstract: We present the results of a radio and X‐ray study of the Galactic microquasar GRS 1758−258, using unpublished archival data and new observations. We focus in particular on the 2000–2002 state transitions, and on its more quiet behaviour in 2008–2009. Our spectral and timing analysis of the XMM–Newton data shows that the source was in the canonical intermediate, soft and hard states in 2000 September 19, 2001 March 22 and 2002 September 28, respectively. We estimate the disc size, luminosity and temperature, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 73 publications
8
39
0
Order By: Relevance
“…We make use of the spectral fitting results from sources in NGC 3379 ) and NGC 4278 . The Local Group sample is based on spectral fits to Galactic (McClintock & Remillard 2005;Soria et al 2011) and M 31 (Trudolyubov et al 2006;Stiele et al 2011) sources with L X adjusted to the 0.5-7.0 keV band using Xspec. Lines of constant BH mass with increasing kT in for 10 M , 5 M , and 2.5 M BH are based on the prescription of Gierliński & Done (2004) and assumptions of Brassington et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…We make use of the spectral fitting results from sources in NGC 3379 ) and NGC 4278 . The Local Group sample is based on spectral fits to Galactic (McClintock & Remillard 2005;Soria et al 2011) and M 31 (Trudolyubov et al 2006;Stiele et al 2011) sources with L X adjusted to the 0.5-7.0 keV band using Xspec. Lines of constant BH mass with increasing kT in for 10 M , 5 M , and 2.5 M BH are based on the prescription of Gierliński & Done (2004) and assumptions of Brassington et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Soria et al (2011) noted that a 2003 INTEGRAL study found N dbb ≈2700 during another soft-state period, which compared poorly to the 1668 value they found, leading them to use an average value of 2200 in their calculations. However, when using the latest calibration and including a reasonable dust scattering model, we find a disk normalization in good agreement with the INTEGRAL results, leading to a2700 2100 10% increase in the inferred BH mass.…”
Section: Black Hole Binaries: Grs 1758-258mentioning
confidence: 94%
“…The diskbb parameters include the disk inner temperature (kT dbb ) and normalization (N dbb ), along with the power-law modelʼs slope (Γ) and normalization (N po ). In all of our fits, we found it necessary to fix the slope of the powerlaw to the value found in Soria et al (2011) in order to reasonably constrain the fits; this may be due to updates in the XMM-Newton calibration. Holding the slope constant also had the effect of artificially reducing the size of the kT dbb error bars, but this is not relevant to our comparison here.…”
Section: Black Hole Binaries: Grs 1758-258mentioning
confidence: 99%
“…3 Such a break can be seen in numerous objects. For example, it is seen at 2 keV in the 2000 outburst of XTE J1118+480 (Hynes et al 2000;Esin et al 2001), at 40 keV in the 2000 outburst of XTE J1550−564 (Rodriguez et al 2003), at ∼70 keV in the 2002 outburst of GX 339−4 (Homan et al 2005), at ≈40 keV in the 2005 outburst of GRO J1655−40 (Joinet et al 2008), at ∼40 keV in the 1991 outburst of Cyg X-1 (Gierlinski et al 1997), and at ∼7 keV in the 2002 outburst of GRB 1758−258 (Soria et al 2011), to name only a few examples. These breaks are most pronounced in the "hardest" state.…”
Section: Introductionmentioning
confidence: 99%